Posterior vault distraction osteogenesis in Apert syndrome - Cassio Raposo-Amaral; Cesar Augusto Raposo-Amaral; Enrico Ghizoni (Brazilian Society for Pediatric Neurosurgery, 2022)
Apert syndrome is an uncommon autosomal dominant condition with a varied clinical spectrum which includes  premature cranial and facial suture fusion and complex upper and lower limb syndactilies. In this manuscript, we share our posterior vault distraction osteogenesis (PVDO) experience regarding Apert syndrome patients so that a larger patient population may benefit. In addition, we aimed to determine an onset of elevated intracranial pressure in the long term follow up. A retrospective study was performed on consecutive patients with syndromic craniosynostosis who were diagnosed with Apert syndrome, underwent PVDO between 2012 and 2019, and received at least 2 years of follow-up care. Demographic data, diagnosis, surgery related data, and outcome data (perioperative and mid-term complications and need for additional surgery), were verified by means of medical records, clinical photographs, radiographic images, and interviews with all included patients and/or their parents. The present study included 14 patients who were diagnosed respectively with Apert syndrome (n = 14). The average posterior advancement distance achieved was 19.37 ± 3.0 mm. Two patients included in this study presented major complications, but neither experienced permanent sequelae or a lethal course. Two Apert patients presented cerebral spinal fluid (CSF) leakage (Clavien-Dindo type II).   One patient presented a onset of elevated intracranial pressure at 4 years of follow up. PVDO is an effective procedure at alleviating intracranial pressure and present a low complication rate.